Efficacy of human immunoglobulin injection and effects on serum inflammatory cytokines in neonates with acute lung injury - Wang, Shaohua; Tang, Zanmei; Zheng, Xuemei; Deng, Jian; Wang, Zhangxing (Experimental and therapeutic medicine, 2021)
The present study aimed to explore the efficacy of intravenous immunoglobulin (IVIG) injection in neonates with acute lung injury (ALI) and assess its effects on serum inflammatory cytokine levels. The research subjects were 140 neonates with ALI who were evenly distributed into a control group (COG) and a study group (STG). The COG patients were treated routinely, whereas patients in the STG were administered IVIG in addition to the standard treatment received by the COG. The arterial partial pressure of oxygen (PaO2), PaO2/fraction of inspired oxygen (FIO2), mechanical ventilation time and hospitalization time were compared between the two groups. ELISA was used to determine the levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in the patients before treatment and at 12, 24 and 36 h after treatment. The Kaplan-Meier method was used to analyze the survival of the patients, including their survival for 30 days after treatment. The patients were divided into high and low cytokine expression groups based on their mean expression levels of serum IL-6 and TNF-α before treatment. After treatment, PaO2 and PaO2/FiO2 were significantly higher and mechanical ventilation and hospitalization time were reduced in the STG in comparison with the COG (all P<0.001). At 12, 24 and 36 h after treatment, serum IL-6 and TNF-α levels in the STG were lower than those in the COG (both P<0.05). The 30-day survival rate after treatment was not significantly different between the two groups (P>0.05). The 30-day survival rate in the high IL-6 and high TNF-α expression COG was lower than that in the low IL-6 and low TNF-α expression COG (both P<0.05). The results of the present study indicate that IVIG may improve pulmonary gas exchange, shorten the course of disease and reduce the inflammatory response in neonates with ALI.